Medical Ethics and the Limits of Patient Autonomy: The Debate on Confesiones de un Médico - García Zabaleta, Omar; Casado da Rocha, Antonio (MEDICA REVIEW. International Medical Humanities Review / Revista Internacional de Humanidades Médicas, 2012)
This paper reviews the debate around the Spanish translation of Alfred Tauber’s “Confessions of a Medicine Man,” whose main topics were already analyzed in a previous issue of this journal. Professionals with diverse backgrounds within the fields of medical humanities have discussed the pros and cons of Tauber’s proposal. Their main arguments have focused on the roles of scientific advances and the concept of autonomy. To clarify and move forward the debate, we propose to establish a concept of autonomy rooted on the nature of the healthcare relationship and its caring role, taking into consideration the biological, cognitive, and moral features that develop in the interaction between the individual and its environment.